1998
DOI: 10.1148/radiology.208.2.9680571
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid hemorrhage: aneurysm detection and preoperative evaluation with CT angiography.

Abstract: CT angiography depicted 90% of all aneurysms, and 90% were classified as definitely present. CT angiography must be of high quality with adequate depiction of the aneurysm and the parent artery for surgery to be performed on the basis of CT angiographic findings alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(57 citation statements)
references
References 0 publications
2
49
1
5
Order By: Relevance
“…However, this seems unlikely because the dominant contribution of aneurysmal SAH in population studies of SAH across many countries, and over time, has remained consistent. [25][26][27][28][29][30] Given these limitations, it is important to acknowledge that our results are discordant from an earlier United Kingdom audit of SAH outcomes 15 undertaken during the transition from an era of surgical clipping to one of mixed modalities of treatment, which showed no effect of volume on mortality, outcome, or case-mix adjusted outcome. However, the United Kingdom SAH audit 15 varied from our study in several features.…”
Section: March 2013contrasting
confidence: 71%
“…However, this seems unlikely because the dominant contribution of aneurysmal SAH in population studies of SAH across many countries, and over time, has remained consistent. [25][26][27][28][29][30] Given these limitations, it is important to acknowledge that our results are discordant from an earlier United Kingdom audit of SAH outcomes 15 undertaken during the transition from an era of surgical clipping to one of mixed modalities of treatment, which showed no effect of volume on mortality, outcome, or case-mix adjusted outcome. However, the United Kingdom SAH audit 15 varied from our study in several features.…”
Section: March 2013contrasting
confidence: 71%
“…Previous studies reported that aneurysms in certain locations such as posterior communicating artery aneurysms, might be missed by CTA (2,27,33). The poor sensitivity in detecting posterior communicating artery aneurysms in these studies was attributed to their small size and their similar morphological characteristics with infindubular dilatations.…”
Section: Discussionmentioning
confidence: 85%
“…Some studies evaluating CTA in the management of intracranial aneurysms have reported sensitivities ranging from 77% and 100% and specificities ranging from 79% and 100% [2,23]. Among aneurysms detected on CTA and then undergoing surgery, 100% correlation was observed between CTA and catheter angiography [26]. CTA, as a less invasive alternative to cerebral angiography, is a widely accepted method for detection and characterization of cerebral aneurysms when planning surgical intervention [27].…”
Section: Preoperative Planningmentioning
confidence: 99%